Protective role of silibinin over nickel sulfate-induced reproductive toxicity in male rats - Temamogullari, F.; Atessahin, A.; Sen, C. Cebi; Yumusak, N.; Dogru, M. S. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2021)
Nickel damages the male reproductive system. We investigated the beneficial effects of silibinin which has metal-chelating and antioxidant properties over nickel toxicity. Both antioxidative effects in testes and overall effects related to sperm motility, membrane and acrosome integrity of orally administered Silibinin were evaluated against the harmful effects of 30 day of intraperitoneal nickel sulfate (5 mg/kg/day) administration in rats. Male rats were randomized into control (Group1; n=6) and three experimental groups (n=6, each): Group2 Nickel sulfate (5 mg/kg/day), Group3 Silibinin (150 mg/kg/day), and Group 4 Nickel sulfate (5 mg/kg/day) + Silibinin (150 mg/kg/day). We found higher sperm motility, viable sperm and total sperm count in Groups 3 and 4 than the Group 2 treatment groups and the percentage of abnormal spermatozoa was similar in both groups (Groups 2 and 4). Increased apoptosis, activation of caspase3, 8, 9 and TUNEL were detected in Group 2. However, activation of caspase3, 8, 9 and TUNEL was reduced in Group 4. The protective effects of silibinin were demonstrated on histopathologic findings and some sperm parameters (sperm motility percentage, viable spermatozoa, sperm count, and abnormal spermatozoa percentage) in rats exposed to nickel.
Keywords: nickel; silibinin; male; rats; reproductive toxicity